Pengembangan SDM Unggul Melalui Program Pendampingan Pendidikan dan Pelatihan di Desa Sendir - Moh. Kurdi; Fatmawati; Bambang Hermanto; Mohammad Anwar (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
The program aims to improve the skills and knowledge of village residents in literacy, numeracy, technical skills, and entrepreneurship through human resource development (HRD) facilitated education and training in Desa Sendir. It begins with needs identification through surveys and interviews with residents and community leaders, revealing urgent needs in basic education and specific skills. Based on these findings, a comprehensive training curriculum was designed and implemented from February to March 2024, covering basic and specialized training according to participant interests. Periodic evaluations showed significant improvements in participant abilities, with 85% showing clear progress. Program adjustments were made to ensure training relevance and effectiveness, followed by the development of local support networks. The dissemination of program results through seminars and online media expanded the program's positive impact. Commitment to program sustainability was implemented through plans for advanced training and local capacity development. The program results indicate that a structured and collaborative approach to education and training can bring significant positive changes to community development in Desa Sendir